The results of clinical application of the spring-loaded fixator in osteosynthesis of the medial fractures of femoral neck - Pirogov, Evgeny; Tyazhelov, Olexiy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2016)
The share of femoral neck fractures in the structure of injuries enlarges every year due to increasing number of elderly people. Known techniques of osteosynthesis do not provide satisfactory results of treatment in the majority of patients with medial femoral neck fractures. The goal: to improve outcomes of treatment for the patients with medial femoral neck fractures through the development and introduction into clinical practice a new method of bone fragments connecting. The methods: a new device for osteosynthesis of medial femoral neck fractures was worked out and implemented into clinical practice; due to its design features this device can provide primary intertrfragmental compression during surgery and secondary due to potential energy of the compressed spring. A special mechanism of ratchet gearing provides unidirectional telescopic effect and prevents the formation of interfragmental diastase that allow to achieve spontaneous fracture stabilization in postoperative period even with substantial edge resorption of fragments. 114 patients (aged from 23 to 92 years) underwent 115 ope-rations using proposed device from February 2011 to July 2015. Results: positive results in the main clinical group, where proposed fixator was used, were obtained in 89 % cases. Conclusions: the device, that was worked out, is substentiated from anatomical-clinical positions and concepts of resorptive process within the remodeling of bone fragments. The technique is highly effective osteosynthesis even under adverse prognostic for bone-healing of medial femoral neck fractures (II–III type by Pauwels, III–IV typeby Garden) in patients of different age groups. Minimally invasive surgery technique enables organ-savings surgery for elderly patients, including those with co-morbidities.